2014
DOI: 10.1364/josaa.31.000935
|View full text |Cite
|
Sign up to set email alerts
|

Why do rough surfaces appear glossy?

Abstract: The majority of work on the perception of gloss has been performed using smooth surfaces (e.g., spheres). Previous studies that have employed more complex surfaces reported that increasing mesoscale roughness increases perceived gloss [Psychol. Sci.19, 196 (2008), J. Vis.10(9), 13 (2010), Curr. Biol.22, 1909 (2012)]. We show that the use of realistic rendering conditions is important and that, in contrast to [Psychol. Sci.19, 196 (2008), J. Vis.10(9), 13 (2010)], after a certain point increasing roughness furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 31 publications
(79 reference statements)
0
39
1
Order By: Relevance
“…Previous research concerning the influence of image cues on material perception have hitherto either used human judgments (Marlow et al, 2012;Marlow & Anderson, 2013) or luminance histogram-based moment statistics (Motoyoshi et al, 2007;Sharan et al, 2008). The former approach appears to be motivated by difficulties designing robust algorithms that capture image properties like coverage, contrast, and sharpness of the highlights (but see also Qi, Chantler, Siebert, & Dong, 2014) for segmentation of highlights based on pixel intensity threshold and pixel wise calculation of the features for the case of rendered surfaces with identical parameters settings). Yet, the drawback of relying on human judgments is that there could be interaction effects (e.g., an object appears glossier, causing the contrast to be perceived higher).…”
Section: Previous Workmentioning
confidence: 99%
“…Previous research concerning the influence of image cues on material perception have hitherto either used human judgments (Marlow et al, 2012;Marlow & Anderson, 2013) or luminance histogram-based moment statistics (Motoyoshi et al, 2007;Sharan et al, 2008). The former approach appears to be motivated by difficulties designing robust algorithms that capture image properties like coverage, contrast, and sharpness of the highlights (but see also Qi, Chantler, Siebert, & Dong, 2014) for segmentation of highlights based on pixel intensity threshold and pixel wise calculation of the features for the case of rendered surfaces with identical parameters settings). Yet, the drawback of relying on human judgments is that there could be interaction effects (e.g., an object appears glossier, causing the contrast to be perceived higher).…”
Section: Previous Workmentioning
confidence: 99%
“…Likewise, a specular surface can appear to have a different 3D structure compared to the same surface geometry rendered with a lower specular reflectance (Doerschner, Yilmaz, Kucukoglu, & Fleming, 2013;Ho et al, 2008;Mooney & Anderson, 2014;Todd & Mingolla, 1983). We have previously shown that these perceptual interactions correlate highly with image properties generated by specular luminance gradients (Marlow & Anderson, 2013;Marlow et al, 2012;Mooney & Anderson, 2014;Qi et al, 2014). Surfaces appear to increase in specular reflectance when there is an increase in the contrast, sharpness, or abundance of specular image structure, regardless of whether it is the surface geometry, reflectance function, or light field that actually generates that structure.…”
Section: Introductionmentioning
confidence: 99%
“…A recurring theme in this literature is that surface geometry and reflectance can affect the perception of each other (e.g., Ho, Landy, & Maloney, 2008;Todd & Mingolla, 1983). Physical differences in shape can induce apparent differences in specular reflectance (Marlow & Anderson, 2013;Nishida & Shinya, 1998;Olkkonen & Brainard, 2011;Qi, Chantler, Siebert, & Dong, 2014;Vangorp, Laurijssen, & Dutré, 2007;Wendt, Faul, Ekroll, & Mausfeld, 2010;Wijntjes & Pont, 2010). Likewise, a specular surface can appear to have a different 3D structure compared to the same surface geometry rendered with a lower specular reflectance (Doerschner, Yilmaz, Kucukoglu, & Fleming, 2013;Ho et al, 2008;Mooney & Anderson, 2014;Todd & Mingolla, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Their result is somewhat similar to that of Beck et al [14] because they illustrated that the accuracy of material depiction is influenced by both the particular shape and the material of the object in the rendering setting. Recently, Qi et al [18] characterized the relationship between surface roughness and the highlight area and stated that the use of realistic illumination conditions is critical for realistic rendering in terms of gloss depiction. Thus, considering only environment illumination, which captures real illumination, is a valid assumption.…”
Section: Human Perception Of Glossmentioning
confidence: 99%
“…Thus, representing small bumps in such structures is an essential factor of surface gloss representation. Qi et al [18] reported that such bumps produce small highlights. These small highlights make rough surfaces appear smooth and sometimes produce shimmering effects when one eye receives a bright highlight and the other does not [27].…”
Section: Limitationsmentioning
confidence: 99%